IMPROVING THE QUALITY OF CADETS THROUGH SELFEFFICACY: A STUDY ON THE INFLUENCE ON LEARNING OUTCOMES - Suprapto, Yuyun; Silk Moonlight, Lady; Eka Prastiya, Fitri; Diana Puspita, Romma (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2026)
This study aims to examine the impact of self-efficacy on the learning outcomes of cadets at the Surabaya Aviation Polytechnic, as an effort to improve the quality of human resources in the aviation sector. Self-efficacy is considered an important non-technical psychological ability in shaping the preparation, adaptability, and professionalism of cadets in facing the demands of the aviation sector. This study uses a quantitative approach with a survey method, namely through the completion of questionnaires by 120 cadets, and the data obtained was then analyzed using linear regression. The results showed that self-efficacy had a positive and significant impact, both individually and collectively, on learning outcomes, with a contribution of 86.1%. These findings indicate that strengthening psychological aspects, especially self-efficacy, is an important part of supporting cadets’ academic success. Therefore, learning and coaching programs that focus on strengthening self-confidence, the ability to face challenges, and independent learning are needed so that cadets are better prepared to face the professional world of the aviation industry.